Redefining Bankruptcy Law: Incorporating the Principle of Business Continuity for Fair Debt Resolution: Mendefinisikan Kembali Hukum Kepailitan: Memasukkan Prinsip Kelangsungan Usaha untuk Penyelesaian Utang yang Adil - Kiemas, Andre; Matheus, Juan; Gunadi, Ariawan (Universitas Muhammadiyah Sidoarjo, 2023)
This study critically examines the inadequacies of the current Indonesian Bankruptcy Law, highlighting the conflicting nature of its debtors' insolvency declaration mandate, as stated in Article 2, verse (1). The research explores the philosophical basis of incorporating the principle of business continuity into future bankruptcy regulations to ensure fair, rapid, transparent, and efficient debt resolution for both debtors and creditors. Employing a normative legal research methodology, the paper investigates the inherent values of justice, legal certainty, and interests, along with general and bankruptcy principles. The study posits that the essence of bankruptcy law is not merely to protect creditors but also to ensure the survival and continuity of debtor businesses. The findings reveal that existing bankruptcy procedures, including insolvency examinations and financial report analysis, could be refined to better safeguard debtor businesses. This paper argues that an explicit elaboration of the business continuity principle in bankruptcy legislation could promote balanced legal protection in insolvency proceedings. The implications of this research can guide legislative reforms, ensuring a more equitable and efficient debt resolution process in the Indonesian bankruptcy system.Highlights: The current Indonesian Bankruptcy Law struggles with issues of fairness and efficiency in resolving debt problems. The principle of business continuity should be explicitly incorporated into bankruptcy legislation to ensure balanced protection for both debtors and creditors. Legal examination mechanisms, such as insolvency examinations and financial report analysis, could be further refined to safeguard debtor businesses more effectively. Keywords: Indonesian Bankruptcy Law, Debt Resolution, Business Continuity, Normative Legal Research, Legal Protection.